The Effects of Credit Growth on Risk and Performance of Conventional Banks in Indonesia - Mery, Mery; Dony, Chalid Abdul (Journal of International Conference Proceedings, 2021)
Indonesia is a developing country with a bank-based country structure. Credit is the largest component of banking assets. Credit growth with the low interest rates and low standard criteria for potential borrowers will have an impact on the credit risk faced by banks. The purpose of this study is to look into the effect of credit growth on the risk and performance of Indonesian conventional banks. This study uses dynamic panel data with the Generalized Method of Moment (GMM) approach. There are 3 hypotheses to be tested: first, the relationship between credit growth and credit risk using a credit loss approach. Second, the relationship between credit growth and bank profitability using a bank interest income approach. Third, the relationship between credit growth and bank solvency using the ratio of capital to assets. The data used in this study is taken from 93 conventional commercial banks registered with the Indonesia Financial Service Authority (Otoritas Jasa Keuangan) in the period of 2009-2019. The results showed that credit growth has a significant negative effect on credit risk and has a significant positive effect on the profitability and solvency of conventional commercial banks in Indonesia.